BUDAYA SEKOLAH DALAM PENGUATAN KARAKTER DISIPLIN SISWA: KAJIAN SISTEMATIS TENTANG PENDEKATAN DAN IMPLEMENTASINYA DI SEKOLAH - Ahmad Zaki Ilman Nasution; Firman Firman; Nurfarhanah Nurfarhanah (LPPM Universitas Cipta Mandiri, 2025)
This study aims to reveal the role of school culture in strengthening students’ disciplinary character at SMA Negeri 17 Padang. Discipline is a fundamental value that must be instilled early to support students’ success in both academic and social aspects. Using a descriptive qualitative approach with a case study design, data were collected through semi-structured interviews and documentation. The findings indicate that school culture is built systematically through SWOT analysis, the formulation of vision and mission, and the implementation of habituation programs integrated into both academic and non-academic activities. The strengthening of disciplinary character is carried out through four main strategies: value habituation, teacher role modeling, student self-actualization through personal development and extracurricular activities, and optimal school management. The disciplinary culture is reinforced through a collective supervision system, reward mechanisms, and the enforcement of sanctions involving all school components. The study concludes that a strong and structured school culture plays a strategic role in shaping students’ discipline, not only through formal regulations but also by touching students’ affective domain, thereby fostering collective awareness of the importance of discipline within the educational environment.